PELAKSANAAN OPER KREDIT KENDARAAN BERMOTOR RODA EMPAT TANPA DIKETAHUI PIHAK PERUSAHAN PEMBIAYAAN KONSUMEN PT BUANA FNANCE TBK BERDASARKAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Rio Julivan Sibarani; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The credit operation under the hands represents a transfer of liabilities from the old debtor to the new borrower to the fiduciary security object, the transfer of this credit without the consent of the creditor, the credit operation under this hand will cause further legal problems because of this without the consent of the creditor. The formulation of the problem is how the implementation of Law Nomber. 42 of 1999 on Fiduciary Guarantee of motor vehicle operations without known to the financing institution, how the legal efforts against credit operations without knowing by the financing institution. The results of this study that the credit operates have been frequent in all finance companies not only in PT. Buana Finance, Tbk the occurrence of this credit operations because the debtor is not able to continue installment payments, so that from the vehicle seized by the PT. Buana Finance Tbk, it is better to operate it to other party, but the problem of vehicle credit operation is done unnoticed by the company so that the debtor has violated Article 23 Paragraph (2) Fiduciary Law, which becomes the obstacle of this problem is the debtor Many do not know the legal consequences caused when doing credit operations unnoticed by the financing institutions in addition to lack of socialization of the company to the problem of credit oper, the vehicle in oper credit to others do not know its existence, and efforts made to overcome the existing obstacles , Where the debtor by giving an explanation to the debtor at the signing of the credit agreement, by explaining the credit operations, asks the old debtor to take responsibility for the transferred vehicle who does not know its existence by paying off the outstanding debtKeyword: take over credit, Four-wheel vehicle, Fiduciary guarantee